Persepsi Konstituen Terhadap Anggota DPRD dalam Meningkatkan Kesejahteraan Masyarakat - Walid Mustafa Sembiring (Universitas Medan Area, 2014)
This study aims to determine how perceptions of the constituents of the legislators in improving public welfare Samosir regency. This research uses descriptive method with the number of population is the whole electorate Samosir who participated in the general elections in April 2009 with a total of 100,000 people. The sample in this study were drawn at random, namely three districts, each district of the village taken 2, drawn 2 of every village and every hamlet Hamlet taken 5 KK. As a sample of 71 households drawn randomly from the District Pangururan, Onanrunggu, Sianjur at first. Data collection techniques in this study is the form of observations, questionnaires and interviews. Data analysis technique used is a simple statistical formula frequency table. The results showed that the respondents to the opinion of members of parliament has not been instrumental in carrying out their duties properly as a member of parliament in improving the welfare of people in Samosir, Samosir district chief along with legislators at the meeting Naidoo establish regulations peripurna Samosir Regency. Samosir District Assembly Members always carry out surveillance on the course of regulation, decree and budget.